Using self-reflection to support teacher professional learning and development of their digital competence: A multi-case study using SELFIEforTEACHERS - Kyza, Eleni A.; Joint Research Centre, Seville; Economou, Anastasia; Georgiou, Yiannis; Kapsalis, George; Gallagher, Sean; Galvin, Conor; Gonida, Eleftheria; Hernandez-Leo, Davinia; Ilomaki, Liisa; Lakkala, Minna; Moustakas, Dimitrios; et al. (My University, 2024)
This report presents a multi-case qualitative research study on how to support teacher professional learning and development of their digital competence, through a self-reflection process using SELFIEforTEACHERS (SfT). The study investigated how SfT can be used in different settings and what factors, enablers and barriers affect its effective implementation. Moreover, it investigated how self-reflection using SfT can support teachers’ agency and efficacy for their professional development in using digital technologies in teaching and learning. The report presents the theoretical assumptions that guided the research and discusses the main pertinent findings across the cases, based on the evidence amassed for the individual case studies. Findings are reported from 13 individual case studies conducted in 6 European Union countries and are based on thematic analyses using an explanatory case study approach. The report concludes with proposed recommendations for teachers, school leaders, teacher trainers and educators, and policymakers.
Keywords: teachers' digital competence